1994
DOI: 10.1007/bf00218909
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of meiosis in XXY germ cells: study of 543 sperm karyotypes from an XY/XXY mosaic patient

Abstract: Human sperm chromosomes from a 46,XY/47,XXY male were obtained using the technique of in vitro penetration of zona-free hamster eggs. The analysis of 543 sperm complements shows a significantly increased incidence (0.9%) of hyperhaploid gonosomal 24,XY sets, with a lack of the expected corresponding gonosomal hypohaploidies, and a normal rate of autosomal non-disjunctions. These results support the suggestion that 47,XXY cells are able to go through meiosis and to form spermatozoa. Only 24,XY sperm chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 16 publications
5
30
2
5
Order By: Relevance
“…The predominate percentage of sex chromosome anomalies among infertile men was attributed to the Klinefelter syndrome (47,XXY), which was the most common karyotypic anomaly to be found among infertile men. Azoospermia is almost the rule in men with Klinefelter syndrome who have the 47,XXY karyotype, although some studies have reported the presence of motile sperm in the ejaculate and testicular sperm in XY/ XXY mosaicism (Cozzi et al, 1994). To avoid the bias, we selected the group of Klinefelter syndrome that is non-mosaic type and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…The predominate percentage of sex chromosome anomalies among infertile men was attributed to the Klinefelter syndrome (47,XXY), which was the most common karyotypic anomaly to be found among infertile men. Azoospermia is almost the rule in men with Klinefelter syndrome who have the 47,XXY karyotype, although some studies have reported the presence of motile sperm in the ejaculate and testicular sperm in XY/ XXY mosaicism (Cozzi et al, 1994). To avoid the bias, we selected the group of Klinefelter syndrome that is non-mosaic type and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…However, spermatozoa from men with mosaic Klinefelter's syndrome contain an extra sex chromosome more often than do spermatozoa from normal men. 15,16 Therefore, there is a possibility that chromosomal errors will be transmitted to the offspring of men with Klinefelter's syndrome. The normal karyotypes of the three infants described here support previously reported data on the safety of intracytoplasmic sperm injection in the treatment of oligospermia and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Except for two cases of mosaicism involving respectively 25% (4/25) and nearly 30% (17/24) of XXY cells (published by Cozzi et al, 1994), the number of abnormal cells was very low, only two, which makes the reality of these mosaics doubtful. This is in agreement with normal sperm concentrations observed in these men of 50 and 240 × 10 6 /ml.…”
Section: Number Of Centresmentioning
confidence: 99%